Accounting in Identity Regulation : Producing the Appropriate Worker - Vaivio, Juhani; Järvenpää, Marko; Rautiainen, Antti (Taylor & Francis, 2021)
It is acknowledged that identity regulation in organizations relies on discursive resources. This study moves beyond discourse – illustrating how discourse and accounting measurements are mobilized together in revising identity. Measurement produces persistence, clarity, transparency and comparability, as well as direction: Accounting’s quantitative knowledge ‘amplifies’ discourse. We explain the Great Alliance between words and numbers in a case study addressing events in an organization’s transformation. This extends our understanding of what takes place on the interface between identity and accounting.
Keywords: Identity regulation; Management control; Performance measurement; discourse; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|